Ovarian hyperstimulation syndrome : epidemiology, pathophysiology, prevention and management - Rizk, Botros (Cambridge University Press, 2006)
Ovarian Hyperstimulation Syndrome (OHSS) can occur in women undergoing in vitro fertilization, after having follicle stimulation hormone (FSH) injections to stimulate egg growth and maturation. This book reviews the important classification, epidemiology, pathophysiology, complications and prediction, prevention and treatment options for this pathology.